Harnessing of plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi in agroecosystem sustainability - Oluwaseun Adeyinka Fasusi; Olubukola Oluranti Babalola; Timothy Olubisi Adejumo (CABI Agriculture and Bioscience)
Abstract Background Soil microorganisms including rhizobacteria and fungi play a key role in soil health, biodiversity and productivity of natural and managed ecosystems. Plant growth-promoting rhizobacteria (PGPR) associated with plant roots enhance the uptake of nutrient and improve productivity. Similarly, mycorrhizal fungi particularly, arbuscular mycorrhizal fungi (AMF), form a mutualistic association with plants and enhance nutrients uptake and consequently promote plant growth and productivity. Methods Here we show how harnessing beneficial soil microorganisms like PGPR and AMF with their positive effect on plant development can contribute to the green and clean economic growth strategy. Results Through a review of the state-of -art knowledge in this area we demonstrate that this approach can improve uptake of nutrients, enhance plant growth, yield and tolerance to biotic and abiotic stress. We argue that this approach can reduce the need for agrochemicals that destabilizes the ecological system. Conclusions This review provides a state-of-the-art synthesis of the knowledge generated so far and insight into the multifunctional strategies employed by AMF and PGPR toward ensuring sustainable agriculture.